Sedimentology for energy transition: SOSGAS project, an example of workflow approach to reservoir quality assessment - César Viseras Alarcón; Patricia Cabello; Luis M. Yeste; Juan Alcalde; Miguel López-Blanco; José L. Cuevas; Marc Gil-Ortiz; Luca Caracciolo; Fernanda De Mesquita Veloso; Niklas Heinemann; Oriol Falivene; Augusto N. Varela; et al. (Geogaceta)
The research workflow employed in the SOSGAS project is presented, aimed at the Quality Assessment as a reservoir of CO2 and green H2 in heterogeneous Mesozoic and Cenozoic fluvial and deltaic formations of the Iberian Plateau and the Ebro and Graus-Tremp Basins. Through the integrated study of outcrop and subsurface data (derived from boreholes drilled behind the outcrops), conceptual models are developed for each examined case, describing variations in sedimentary heterogeneities. These models contribute to the static modeling of different geobodies and their petrophysical properties. Finally, dynamic modeling, based on gas injection simulation experiments (CO2 and H2) into static models, enables the analysis of the sustainability of geo-storage projects for these key fluids in the energy transition.